HUBUNGAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR PESERTA DIDIK DI SMP AL-IKHLASH CIKAWUNG - Kurniasih, Imas; Aryani, Eka (INTIHA: Islamic Education Journal, 2023)
Parents' attention is to focus on the behavior that students receive, by providing supervision and meeting basic needs, giving special attention to supporting learning activities, which is expected to improve student learning achievement (Slameto 2021). This research aims to determine: 1) Parental attention, 2) Student learning achievement, and 3) examine the relationship between parental attention and student learning achievement. This research uses a quantitative approach with correlational research methods. The sampling technique was Random Sampling technique with a sample size of 30 respondents. Data collection techniques are the Parental Attention questionnaire and the Learning Achievement questionnaire. Data analysis with the help of the IBM Statistics SPSS 23 application. The results of this study show that 1) Parental attention at Al-Ikhlash Cikawung Middle School is in the medium category, with an average of 3.4873. 2) The learning achievement of students at Al-Ikhlash Cikawung Middle School is in the high category, with an average of 3.5725. 3) The significant value is 0.235 and the correlation coefficient is 0.211, so Ho is accepted and Ha is rejected. With this, parental attention and learning achievement at Al-Ikhlash Cikawung Middle School have a positive and insignificant relationship. This shows that increasing parental attention will be followed by an increase in student learning achievement.